ANALYSIS OF THE EFFECTIVENESS OF ZAKAT, INFAQ, AND SHADAQAH UTILIZATION ON THE EMPOWERMENT OF MUSTAHIQ IN LAZISMU PAMEKASAN - Matnin, Matnin (Ngejha, 2023)
This study aims to find out how the pattern of zakat utilization is applied in LAZISMU, which is also a model applied in the empowerment of mustahik. With a trusted, professional, and transparent work culture, the Muhammadiyah Amil Zakat Infaq and Shadaqah Institution (LAZISMU) Pamekasan Regency is trying to develop itself into a trusted Zakat Institution. The research method used in this study is a qualitative research method, where the data analysis technique used in this study is data reduction, where all data and information obtained are sorted first before being outlined in the research discussion. The results of the study show that there is a need to maximize training and coaching programs to improve the economy of Duafa. In the utilization of zakat, LAZISMU, in addition to distributing it itself, also always optimizes the Assembly, Institutions, and Ortom within Muhammadiyah so that it has a wider impact on the beneficiaries and the programs are more varied.